Increased risk of hepatobiliary cancers after hospitalization for autoimmune disease - Castro, Felipe A.; Liu, Xiangdong; Försti, Asta; Ji, Jianguang; Sundquist, Jan; Sundquist, Kristina; Koshiol, Jill; Hemminki, Kari (Clinical gastroenterology and hepatology, 2014)
Background & Aims - Some autoimmune diseases are associated with increased risk of liver cancer. However, there has been no comprehensive evaluation of autoimmune diseases among patients who develop different subtypes of hepatobiliary cancer. We examined the association between autoimmune diseases and cancers of the liver and biliary tract in the Swedish population. - Methods - We analyzed data from national datasets at the Center for Primary Health Care Research (Lund University, Sweden). Data on patients with autoimmune disorders were retrieved from the Swedish Hospital Discharge Register, from 1964 through 2008; 33 diseases were evaluated. Hepatobiliary cancer cases were retrieved from the Swedish Cancer Registry. We calculated standardized incidence ratios (SIRs) and hazard ratios for incident cancers and deaths from hepatobiliary cancers. - Results - Among 402,462 patients with autoimmune disorders, 582 were diagnosed with primary liver cancer, 330 with gallbladder cancer, 115 with extrahepatic bile duct cancer, and 43 with ampulla of Vater cancers. We identified 14 autoimmune conditions that were significantly associated with increased risk of primary liver cancer (overall SIR [any autoimmune disease], 2.1; 95% confidence interval [CI], 2.0-2.3), 5 conditions associated with gallbladder cancer (overall SIR, 1.3; 95% CI, 1.1-1.4), and 3 associated with extrahepatic bile duct cancer (overall SIR, 1.6; 95% CI, 1.3-1.9). The autoimmune disorders with the strongest association with primary liver cancer were primary biliary cirrhosis (SIR, 39.5; 95% CI, 28.2-53.8) and autoimmune hepatitis (SIR, 29.0; 95% CI, 9.1-68.2); ulcerative colitis was strongly associated with extrahepatic bile duct cancer (SIR, 5.6; 95% CI, 3.6-8.4). Celiac disease, Crohn’s disease, systemic sclerosis, and ulcerative colitis were associated with at least 2 types of cancer. Increased hazard ratios were observed only for patients with biliary tract cancer who had been hospitalized for autoimmune conditions. - Conclusions - In a study of the Swedish population, we identified an increased risk of hepatobiliary cancers among individuals diagnosed with autoimmune disease. Associations among different cancer types indicate that shared immunomodulatory mechanisms determine susceptibility to hepatobiliary cancer.
Available online: 15 November 2013
Gesehen am 16.03.2021